2021
DOI: 10.1002/jcc.26540
|View full text |Cite
|
Sign up to set email alerts
|

The best density functional theory functional for the prediction of 1H and 13C chemical shifts of protonated alkylpyrroles

Abstract: The prediction of 13C chemical shifts can be challenging with density functional theory (DFT). In this study 39 different functionals and three different basis sets were tested on three neutral alkylpyrroles and their corresponding protonated species. The calculated shielding constants were compared to experimental data and results from previous calculations at the MP2. We find that the meta‐hybrid functional TPSSh with either the Pople style basis set 6‐311++G(2d,p) or the polarization consistent basis set pc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Working on a set of monoprotonated alkylpyrroles, a large set of functionals and basis sets were tested [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Working on a set of monoprotonated alkylpyrroles, a large set of functionals and basis sets were tested [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…[70,71,291,292] Examination of the performance of various XC functionals implied for the calculations of NMR chemical shifts and spin–spin coupling constants can be found in a number of related publications. [ 125–132 ]…”
Section: Nmr Relativistic Methods—a Brief Overviewmentioning
confidence: 99%
“…[70,71,291,292] Examination of the performance of various XC functionals implied for the calculations of NMR chemical shifts and spin-spin coupling constants can be found in a number of related publications. [125][126][127][128][129][130][131][132] Incorporating relativistic effects into the DFT theory applied for the calculation of NMR properties of compounds containing heavy elements (those like mercury) has become a top priority at present. In this sense, the DFT method is likely to be the best candidate for the extension to the relativistic domain given that DFT provides a reliable description of the electron correlation effects in the calculations of NMR parameters with a very small computational computational cost similar to that of the Hartee-Fock method.…”
Section: Nmr Relativistic Methods-a Brief Overviewmentioning
confidence: 99%
“…Semenov and Krivdin 26 benchmarked DFT calculations of 13 C NMR chemical shifts of some natural antimalarial compounds with a new basis set, named 3z-S, and also proposed lower cost NMR computations of large strychnobaillonine molecule. 27 Sauer et al 28 reported on TPSSh as the best density functional combined with 6-311þ þ G(2d,p) basis set for predicting 1 H and 13 C chemical shifts of protonated alkylpyrroles. The impact of relativistic effect on 13 C NMR shielding in carbide-bridged complexes was studied theoretically.…”
Section: Theory and Development Of Toolsmentioning
confidence: 99%